Isolation and Characterization of Total Heterotrophic Bacteria and Exopolysaccharide Produced From Mangrove Ecosystem - Lakshmipriya, V P (International Journal of Pharmaceutical & Biological Archive, 2012)
Isolation and Characterization of Total Heterotrophic Bacteria and Exopolysaccharide Produced From Mangrove Ecosystem